Kajian Dampak Pembangunan Pembangkit Listrik Tenaga Sampah (PLTSA) di Kota Surakarta - Francisco Amaral; Muhamad Edwin Zulfikar Atmani Wedhana; Budi Purwanto; Setyohadi Pratomo; Junjung Sahalatua Manik (Badan Riset dan Inovasi Daerah Kota Surakarta, 2023)
Power Plant is a tool to generate electricity by converting potential energy into mechanical energy which eventually turns into electrical power. The sources of power for electricity generation in Indonesia generally use hydro and wind power. The existence of excessive accumulation of waste in several cities or regencies has given rise to an idea/breakthrough for another use, namely the Garbage Power Plant (PLTSa). PLTSa is a Government program as an effort to utilize clean and renewable energy, and is one form of Indonesia's commitment that has agreed on a global methane pledge to reduce methane gas emissions by 30% by 2030.